Akibat Hukum Akta Notaris Yang Tidak Memenuhi Pasal 38 Undang-Undang Nomor 2 Tahun 2014 Tentang Jabatan Notaris - Anhar, Hanifah Indriyani (Officium Notarium, 2024)
The actions of Notary and PPAT officials must comply with the provisions of Article 38 of the UUJN-P, not only regarding the certainty of the date but also the numbering. However, in case No. 530/Pdt.G/2016/PN. Dps. states that the actions are contrary to Article 15 paragraph 1 of Law No. 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning the Position of Notary. This research includes normative legal research. Data collection or processing techniques that support and are related to this research are document studies. The approach used in legal research that will be carried out is a statutory approach. Analysis of legal materials using qualitative descriptive methods, all collected data is analyzed qualitatively with an inductive nature. The legal consequences of a notarial deed that does not comply with the provisions of Article 38 UUJN are that the deed has evidentiary value as a private deed and if any of the parties does not recognize the deed, it makes the deed null and void because it does not comply with Article 1320. The Notary's responsibility is not fulfilled for a notarial deed made not based on Article 38 UUJN, the Notary is responsible for carrying out obligations, fulfilling the agreement in the peace, completing the deed process with the applicable procedures and legal regulations based on UUJN by immediately giving a number and date to the deed of sale and purchase agreement and the deed of power of attorney to sell.